Identifying the level of knowledge about sports injuries among students: The level of knowledge about sports injuries among third and fourth-year students at the Colleges of Physical Education and Sports Sciences in Baghdad and Al-Mustansiriya - Saloumi, Asst.Prof.Dr. Emad Daoud; فرحان, م.م سجى ثامر; Jassim, L. Amjad Nassif (Sulaimani Journal for Humanities, 2026)
The level of sports knowledge regarding sports injuries is the preferred method for students because of its significant impact, according to the requirements of the practical lessons for the two subjects, in promoting and increasing sports practice. Therefore, the current study aimed to identify the level of knowledge about sports injuries among students in the two stages and thus identify the differences in knowledge according to the two stage variables (third and fourth). Accordingly, it was necessary to build a knowledge test for students and practitioners of sports activities, as it is the main tool for the current research. To achieve the objectives, the researchers applied the tool using the descriptive method on a sample of (357) male and female students for the academic year (2024-2025). The test included (100) statements using five answer alternatives (always applies to me, often applies to me, sometimes applies to me, rarely applies to me, never applies to me) distributed over nine dimensions. After several field procedures represented in building the test and ensuring its validity, conducting the main experiment (applying the test), and processing the data using appropriate statistical methods to process the results, the researchers reached the following results: Students in the two stages have a low level of knowledge about sports injuries and there is no difference in knowledge among the research sample in light of the two variables (dimensions of the scale and the two stages). The test in its final form included (43) statements, achieving a validity coefficient of (92.0) and a reliability coefficient of (0.82). The results led to the construction of a test for the students’ level of mathematical knowledge about sports injuries.